Evaluation of BACTEC MGIT 960 System for Testing Susceptibility of Mycobacterium tuberculosis to First-Line Drugs in China - Zhao, Ping; Fang, Fang; Yu, Qin; Guo, Jiao; Zhang, Jian-hua; Qu, Jifu; Liu, Yingjie (PLOS ONE, 2014)
Background The purpose of this study was to evaluate the performance of the BACTEC MGIT 960 (M960) system compared with the proportion method (PM) on Löwenstein-Jensen (L-J) medium in a peripheral laboratory in China for the testing of Mycobacterium tuberculosis (MTB) susceptibility to streptomycin (SM), isoniazid (INH) rifampicin (RIF) and ethambutol (EMB) a combination known as SIRE. Methods The susceptibility of 205 clinical isolates of MTB to SM, INH, RIF and EMB was performed with the M960 system. The drugs were tested at the following concentrations: 1.0 µg/ml for SM, 0.1 µg/ml for INH, 1.0 µg/ml for RIF, and 5.0 µg/ml for EMB. The results were compared with those obtained by the L-J PM. The L-J PM at an arbiter site was used to resolve any discordant results. Results The overall consistency was 96.6% and concordance values were 95.6% for SM, 97.6% for INH, 98.0% for RIF and 95.1% for EMB. The overall sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of the M960 system for PM (the standard method) was 95.6%, 97.3%, 96.2% and 96.9% respectively, and the sensitivity were 93.3% for SM, 96.9% for INH, 97.4% for RIF and 94.6% for EMB, the specificity were 96.9% for SM, 98.2% for INH, 98.4% for RIF and 95.5% for EMB, the PPV were 94.6% for SM, 97.9% for INH, 97.4% for RIF and 94.6% for EMB, the NPV were 96.2% for SM, 97.3% for INH, 98.4% for RIF and 95.5% for EMB. The turnaround time with the M960 system (median 8.0 days, ranged from 5 to 14 days) was significantly shorter than that with the PM (28 days or 42 days). Conclusion There was a substantial degree of agreement between the two methods. The M960 system was a reliable and rapid method for SIRE susceptibility testing of tuberculosis in China.